PENDIDIKAN SEKS DALAM PERSPEKTIF ISLAM (Analisis Teks Ayat Alquran) - Rini Rahman; Indah Muliati (Islam Transformatif : Journal of Islamic Studies, 2018)
Sex education in Islam is not new. Because when speaking aqidah, worship and morality, there is sex education included in thaharah discussions. Sex education in Islamic perspectives here is an effort to provide knowledge about biological changes in humans, reproductive organs and their functions and how to maintain the reproductive organs they have by instilling moral, ethical and Islamic religious commitments so that they do not occured abuse of reproductive organs. The purpose of sex education in Islam is to maintain the safety and honor and purity of the generation of Islam in the midst of society. Sex education is also given to humanity, so that they do not fall into the abyss of mischief, namely adultery.